White cord syndrome: A rare complication of adequate spinal cord decompression. A case report and review of current literature - Daan N. de Groot; Kennedy Ogenio; F. Yaney Jiang; Niels A. van der Gaag (Brain and Spine)
Introduction: This study presents a rare complication following surgery for cervical spinal stenosis, known as white cord syndrome. This complication is characterized by sudden postoperative neurological deterioration and unique radiological features. Research question: Our aim is to provide an overview of white cord syndrome, its management, and prognosis based on a case study and literature review. Materials and methods: We describe the case of an 82-year-old woman who developed near-complete tetraplegia following a cervical laminectomy from C3 to C6 for a cervical stenosis. In addition, a literature review was conducted, identifying 25 reported white cord syndrome cases. Results: Postoperative MRI revealed no hemorrhage or residual stenosis but showed a new intramedullary T2 hyperintense signal, indicative of white cord syndrome. The patient’s neurological function improved significantly over three months after blood pressure augmentation, dexamethasone administration, and intensive rehabilitation. Review of the literature suggests that white cord syndrome is a rare complication, often presents as immediate postoperative deficits, and is managed primarily through dexamethasone and adequate spinal cord perfusion. Recovery is generally favorable but variable, with MRI changes often persisting despite clinical improvement. Conclusion: White cord syndrome is a rare but serious complication following spinal decompression surgery, requiring prompt diagnosis and intervention. The exact pathophysiology remains unclear. Despite its rarity, it is crucial for clinicians to be aware of this condition so that diagnosis and treatment—encompassing adequate spinal cord perfusion, dexamethasone administration, and physiotherapy—can be promptly initiated. This also highlights the importance of patient education on potential postoperative risks.